Submerged breakwaters design development based on artificial oyster reef - C. Ketsiri; D. Kositgittiwong; C. Ekkawatpanit (Lowland Technology International, 2018)
Due to the problem on coastal erosion is getting more severe currently, there should be the study on the potential impacts of coastal protection structures on the erosion and sediment movement on areas under influence of currents, tides and storm surges. The various kinds of coastal structures can be applied to solve, or at least, to reduce these problems. The present study focuses on detached breakwaters and artificial reefs which are classified as Low crested and submerged structures (LCS). It is used also to provide reducing for the hydraulic loading to become required level where the dynamic equilibrium can be maintained at the shoreline. To accomplish the mentioned goal, the design of LCS structures is needed to allow the transmission of a definite amount of wave energy over the structure by overtopping and also letting transmission occurred through the porous structure. Not only the term of mechanism but also the nature dynamics of the ecosystem are considered to create flexible and sustainable infrastructure while enhancing nature values. The coastal protection measures by using nature and natural processes are expected to have positive impact not only in nature and safety but also in other functions such as recreation or economy. In the present study, artificial oyster reef in Oesterdam, The Netherlands, is studied based on the geometric form, movement of particle shells inside, composition of structure of oyster reef related with the ability to reduce the wave energy.